Temporary impact of blood donation on physical performance and hematologic variables in women. Issue 8 (28th April 2017) - Stangerup, Ida; Kramp, Nana L.; Ziegler, Andreas K.; Dela, Flemming; Magnussen, Karin; Helge, Jørn Wulff
Abstract : BACKGROUND: No former studies have examined how blood donation influences physical performance in women, who due to menstruation may have a slower recovery of performance. Therefore, the aim of this study was to clarify how VO2peak, time trial (TT) performance, and hematologic variables are affected in 18 iron‐sufficient (plasma ferritin [P‐ferritin] > 30 µg/L) women after a standard 450‐mL blood donation. STUDY DESIGN AND METHODS: VO2peak, TT performance, and blood variables were measured at baseline and 3, 7, 14, 21, and 28 days after blood donation in 18 iron‐sufficient women. Anthropometrics were measured at baseline and Day 28. RESULTS: VO2peak was reduced by 7.5 ± 1.1% from 2973 ± 87 mL/min at baseline to 2765 ± 73 mL/min 3 days after blood donation and remained below baseline until 28 days. The TT performance was reduced by 5.2 ± 1.0% from baseline (868 ± 31 sec) to Day 3 (915 ± 29 sec), but was not different from baseline 14 days after blood donation. Blood hemoglobin (B‐Hb) concentration declined by 7.6 ± 2.1% from 8.4 ± 0.1 to 7.8 ± 0.1 mmol/L at baseline and on Day 3, respectively. P‐ferritin at baseline was 58 ± 7 µg/L and it decreased (55 ± 3%) to a nadir of 24 ± 3 µg/L 28 days after blood donation and remained lower at 36 ± 4 µg/L after 90 days. CONCLUSION: VO2peak and B‐Hb were only recovered 28 days after a blood donation whereas TT performance was back to baseline 14 days after blood donation.